THE TAIWAN ISSUE IN THE MASS MEDIA OF THE FUJIAN PROVINCE - Lisha, Fu; Safonova, Olga; Nikonov, Sergey; Labush, Nikolai; Zhao, Yonghua (Revista Inclusiones, 2019)
The Chinese mass media differ from some countries in the global media development system. This is due to economic, cultural and socio-political factors. The Chinese mass media are currently experiencing major structural changes caused by new media trends. The emergence of new media has changed the news industry, primarily under the influence of external factors. The study of the socio-cultural dynamics of modern Chinese mass media is relevant and timely. The regional press in China, which includes the Taiwanese mass media, is of particular interest.